(untitled) (Research, Society and Development, 2023)
The objective of this study was to analyze the processes of requesting medications for the treatment of asthma and chronic obstructive pulmonary disease (COPD), from the Specialized Component of Pharmaceutical Assistance (CEAF) in a small-sized municipality in southern Minas Gerais, Brazil. This was a cross-sectional study, approved by the Research Ethics Committee of the Universidade Federal de Alfenas. The municipality of Campos Gerais-MG was taken as reference for the collection, carried out in the Integrated System of Management of Pharmaceutical Assistance (SIGAF), referring to asthma and COPD prescription data in the period from March 2019 to March 2021. Data were collected regarding the sociodemographic identification of patients and medication request: request result (granted, rejected, or partially rejected) and reason for rejection. A total of 61 patients and 77 prescriptions were obtained. Most of the requests were considered granted (68.83%), but there was a significant rate of denials (28.57%). Among the refusals, the most prevalent reasons were "prescribed drug not consistent with the stage of the disease" (31.82%), "patient not included in the criteria of current legislation" and "posology inconsistent with Clinical Protocol of Therapeutic Guidelines" (both with 22.73%). The results of this study highlight the negative impact that denials can have on the patient’s health and well-being. It was evidenced that in the municipality studied there is a high prevalence of denials related to asthma and COPD drug treatment, most of them due to avoidable errors. Future studies should seek the evaluation of other fields of the SIGAF and the impact of refusal of prescriptions on other levels of Pharmaceutical Surveillance.